2021
DOI: 10.1016/j.ejca.2021.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Early ctDNA response to chemotherapy. A potential surrogate marker for overall survival

Abstract: The aim of the study was to compare ctDNA response rate and objective response rate as surrogate markers for overall survival (OS) in patients with metastatic cancer treated with chemotherapy. Methods: The study included 420 patients distributed in five cohorts with colorectal, ovarian, and nonesmall cell lung cancer. It represents a retrospective analysis of patients enrolled in prospective biomarker studies and clinical trials. All patients had ctDNA measured before start of treatment and at the first evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…An emerging interest in plasma ctDNA assays lies in their ability to be used as an early marker of response to systemic therapy in mCRC. Here, several groups have shown that reductions in ctDNA following initiation of chemotherapy (as early as after 1 cycle) was prognostic for improved survival and predictive of tumor response when correlated to CT responses as early as 8-10 weeks after chemotherapy initiation [125][126][127][128][129][130][131]. These findings have been concordant in the prospective PLACOL study where mCRC patients treated after cycle 1 of chemotherapy having low (≤0.1 ng/mL) plasma concentrations of methylated ctDNA experienced improved OS and higher objective response rates [132].…”
Section: Response To Systemic Therapymentioning
confidence: 99%
“…An emerging interest in plasma ctDNA assays lies in their ability to be used as an early marker of response to systemic therapy in mCRC. Here, several groups have shown that reductions in ctDNA following initiation of chemotherapy (as early as after 1 cycle) was prognostic for improved survival and predictive of tumor response when correlated to CT responses as early as 8-10 weeks after chemotherapy initiation [125][126][127][128][129][130][131]. These findings have been concordant in the prospective PLACOL study where mCRC patients treated after cycle 1 of chemotherapy having low (≤0.1 ng/mL) plasma concentrations of methylated ctDNA experienced improved OS and higher objective response rates [132].…”
Section: Response To Systemic Therapymentioning
confidence: 99%
“…However, the cohort sizes of the two above phase II studies [ 26 , 36 ] were rather small ( n = 32 and n = 23, respectively) as in the present study. Jakobsen et al [ 37 ] found a prognostic impact of meth-HOXA9 in ovarian cancer and late-stage NSCLC patients. This was supported by Wen et al [ 24 ] reporting a prognostic impact at baseline and after one treatment cycle analysing 231 late-stage NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies across cancer types define early dynamics to occur within the first 3 months. 15,19,22 A recent study on metastatic breast cancer analyzing blood sampled at baseline and once during treatment (between 4 and 12 weeks) found that the one ctDNA analysis after treatment initiation held significant prognostic information and correlated with the later radiologic assessment. 23 In advanced melanoma, Syeda et al 9 reported an independent prognostic value of ctDNA.…”
Section: Assessment Of Ctdna Dynamicsmentioning
confidence: 99%
“…The effect of early changes in the level of ctDNA was also found in a study by Thomsen et al 37 Colorectal cancer patients treated with chemotherapy who had an undetectable level of ctDNA after the first treatment cycle had a median survival of 25.4 months compared to 13.5 months in the group with detectable ctDNA. Another study 22 investigated the correlation between ctDNA level at the first evaluation of objective response and prognosis. An undetectable level or a level with a lower confidence interval (CI) including zero correlated with OS in all 4 cohorts (ie, colorectal, ovarian, and lung cancer).…”
Section: Introductionmentioning
confidence: 99%